Localized immunoglobulin light chain amyloidosis: Novel insights including prognostic factors for local progression. Issue 10 (12th August 2020) - Basset, Marco; Hummedah, Kamal; Kimmich, Christoph; Veelken, Kaya; Dittrich, Tobias; Brandelik, Simone; Kreuter, Michael; Hassel, Jessica; Bosch, Nikolaus; Stuhlmann‐Laeisz, Christiane; Blank, Norbert; Müller‐Tidow, Carsten; et al.
Abstract: In localized light chain amyloidosis (locAL), amyloidogenic light chains (aLC) are produced and deposited locally by a B‐cell clone. We present 293 patients with immunohistochemically confirmed locAL. Lung (nodular pulmonary) with 63 patients was the most involved organ. The aLC was λ in 217 cases (κ:λ ratio 1:3). A local B‐cell clone was identified in 30% of cases. Sixty‐one (21%) had a concomitant autoimmune disorder (cAD). A monoclonal component (MC) were present in 101 (34%) patients and were more frequent in subjects with cAD (51% vs 34%; P = .03). Cigarette smoking was more prevalent in lung locAL (54% vs 37%; P = .018). After a median follow‐up of 44 months, 16 patients died and 5‐ and 10‐years locAL progression‐free survival (PFS) were 62% and 44%. Interestingly, locAL‐PFS was shorter among patients with an identified clonal infiltrate at amyloid deposition site (40 vs 109 months; P = .02) and multinuclear giant cells and/or an inflammatory infiltrate resulted in longer locAL‐PFS in lung involvement (65 vs 42 months; P = .01). However, no differences in locAL PFS were observed in patients with cAD, a MC and involved organ site. Treatment was administered in 163 (54%) patients and was surgical in 135 (46%). Median locAL‐PFS after first treatment was 56 months. Responders had longer locAL‐PFS (78 vs 17 months; P < .001). Three patients with lung locAL and a MC were diagnosed as systemic AL amyloidosis at follow‐up. In summary, locAL pathogenesis seems to be heterogeneous and the clonal infiltrate leads local progression.